The Effectiveness of Digital Sports Communication in Mental Motivation and Some Volleyball Skills For Female Students - Mona Talib Al-Badri; Haneen Mohamed Hussein; Ayman Hani Abdel-Jubouri (Indian Journal of Forensic Medicine & Toxicology, 2021)
This research aims to identify the following: Preparing a curriculum according to digital sportscommunication. Identifying the impact of the effectiveness of a program for sports digital communicationon mental motivation and some volleyball skills for students. The experimental method was used with thedesign of one group, as the research community was determined by the fourth stage students of the Collegeof Physical Education and Sports Sciences at the University of Kufa for the academic year 2020-2021,of which (21) female students, then, the mental motivation scale and the skills of the volleyball test wereapplied to them, also appropriate statistical treatments were used to reach the results. After that, the resultswere presented, analyzed and discussed. The following were achieved:1.Using the curriculum according to a digital sports communication program has a positive effect on themental motivation and some volleyball skills of the female students.2. The use of the curriculum according to a program for digital sports communication is better than themethod used, which increased mental motivation and some volleyball skills for female students.3. The curriculum according to a program for digital sports communication had the effect of controlling theaccuracy and correct performance of skills.Based on the results of the research, the researchers reached the most important recommendations:1. Adopting the curriculum according to a program for digital sports communication a positive effect on themental motivation and some volleyball skills of the female students.2. Reliance on modern means of communication as an essential part of the content of the educationalcurriculum for skills in volleyball.